Can an Integrated System of Electroencephalography and Virtual Reality Further the Understanding of Relationships Between Attention, Meditation, Flow State, and Creativity?. (July 2019) - Yang, Xiaozhe; Cheng, Pei-Yu; Lin, Lin; Huang, Yueh Min; Ren, Youqun
The creativity of the brain is usually measured by one's creative behavior or activity. This study explores connections between an individual's creative behavior and his or her creative brain by asking each participant to design an open-ended virtual product in an integrated system consisting of virtual reality and brainwaves. The results show a significant correlation between the individual creativity level and the state of flow. There is a significant correlation between the state of flow and the quality of the creative product. The attention value is correlated significantly with the quality of product. The participants' four different behaviors significantly demonstrated different attention and meditation levels. The sequential analysis shows that people with high product creativity have a higher attention value while maintaining a state of relaxation, demonstrated during the behavior of painting in the virtual reality environment. Given a limited period of time, a higher level of product creativity can be achieved through persistent implementation, concentration, and by being relaxed both physically and mentally. Implications of the study on teaching, learning, and designing a creative learning environment will be discussed.